2011
DOI: 10.3390/ijerph8072758
|View full text |Cite
|
Sign up to set email alerts
|

High Tobacco Use among Lesbian, Gay, and Bisexual Populations in West Virginian Bars and Community Festivals

Abstract: With no information on tobacco use for lesbian, gay, or bisexual (LGB) populations in West Virginia (WV), it is unclear if nationally-identified LGB tobacco disparities also exist in this State. To address this data gap, we conducted a community tobacco survey in bars and events associated with the WV Pride Parade and Festival. Trained community surveyors used electronic and paper survey instruments in bars (n = 6) in three WV cities and community events associated with the WV Pride Parade and Festival. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…34,35 A systematic review of 42 studies on tobacco use among these groups in the US found a significantly higher risk of smoking among sexual and gender minorities compared to the general population (OR = 1.5 to 2.5). 26 In addition to the same risk factors for smoking that confront other groups, sexual and gender minorities also face additional factors that exacerbate their risk, including social environments that are accepting of smoking, 27,36,37 aggressive targeting by the tobacco industry, [38][39][40][41][42] and perhaps most notably stigma-related processes including minority stress, psychological distress, and social isolation. 24,26,[29][30][31]39,[43][44][45][46][47][48][49] The alarmingly high risk of smoking among sexual and gender minorities together with research that has documented a relationship between stigma-related processes and smoking prevalence for these groups raises questions about whether tobacco-related stigma intensifies the disadvantages associated with the stigmas of other social identities.…”
mentioning
confidence: 99%
“…34,35 A systematic review of 42 studies on tobacco use among these groups in the US found a significantly higher risk of smoking among sexual and gender minorities compared to the general population (OR = 1.5 to 2.5). 26 In addition to the same risk factors for smoking that confront other groups, sexual and gender minorities also face additional factors that exacerbate their risk, including social environments that are accepting of smoking, 27,36,37 aggressive targeting by the tobacco industry, [38][39][40][41][42] and perhaps most notably stigma-related processes including minority stress, psychological distress, and social isolation. 24,26,[29][30][31]39,[43][44][45][46][47][48][49] The alarmingly high risk of smoking among sexual and gender minorities together with research that has documented a relationship between stigma-related processes and smoking prevalence for these groups raises questions about whether tobacco-related stigma intensifies the disadvantages associated with the stigmas of other social identities.…”
mentioning
confidence: 99%
“…pride events) than heterosexual and bisexual peers [14]. Other studies conducted in western countries found that bisexual (compared to heterosexual) identity is associated with smoking [22,23],which may suggest that bisexual youth in China may be less likely than those in western countries to take ''bar culture'' as a primary means of socialization and cope with the stress resulting from homophobia by smoking [24]. Several studies have found that cigarette smoking may be adopted by sexual minorities, especially younger adolescents, to cope with negatively feelings related to having a sexual orientation that is socially stigmatized [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…22,23,54 None, however, sought to elucidate associations to minority stress that might be more prominent for sexual minorities in the rural setting. The participants in our study endorsed their own assumption of minority stress, noting both stressors they experienced as sexual minorities in Appalachia and the predominant role that stress played in smoking behaviors, though many did not perceive that tobacco use was higher among LGB persons than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…17–19 Various studies conducted in urban settings have demonstrated high rates of smoking among sexual minority populations in the United States. 3,6,20,21 Smoking prevalence among rural LGB persons is not well established but at least two studies provide evidence that in some areas the proportion of current smokers among LGBT in a rural state or rural areas of a state (45–46%) 22,23 exceeds even the general Appalachian rate (34%), 15 though no studies offer direct comparisons. Given the paucity of population-based surveys that include questions about sexual orientation, the actual patterns of smoking and tobacco use among rural sexual minorities remain unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation